Development of Digestive Enzyme of Patin Pangasius hypohthalmus Larvae - Effendi, I.; Augustine, D.; Widanarni, . (Indonesian Society of Scientific Aquaculture (ISSA), 2006)
Culture of patin Pangasius hypophthalmus especially larval rearing very depends on the supply of natural food as energy source. Artemia is the main natural food for fish larvae as a starter food, but its price is high. To reduce production cost, farmers tend to reduce the feeding frequency and shorten the Artemia feeding period. Altering feeding regime however may reduce fry quality. This relate to the availability of digestive enzymes. The objective of this study was to examine digestive enzymes activity in patin larvae fed with different feeding regime. By shorten feeding period with Artemia to 2-4 days and Tubifex,substitution, the enzymes activity of protease, lipase and amylase were revealed similar pattern The enzymes activity tends to increase and reach the peak at day 7 , and decrease later on until day 15 after hatching. Survival rate of fish were varied for each treatment, and the highest survival rate was obtained when larvae were fed by Artemia for 8 days. Blood worm were not fully digested by patin larvae at early stage. Keywords: enzyme, digestion, patin, Pangasius hypophthalmus ABSTRAK Proses budidaya ikan patin, Pangasius hypophthalmus terutama pembenihan sangat tergantung oleh ketersediaan pakan alami sebagai sumber energinya. Artemia merupakan pakan alami yang banyak diberikan pada saat larva ikan mulai makan, namun harganya relatif tinggi. Untuk menekan biaya produksi, petani ikan patin cenderung mengurangi frekuensi pemberian Artemia dan mempersingkat waktu pemberiannya. Penggeseran jadwal ini diduga mengakibatkan penurunan kualitas benih ikan patin yang dihasilkan yang berhubungan dengan kesiapan enzim pencernaannya. Penelitian ini dilakukan untuk mengetahui aktivitas enzim pada larva ikan patin dengan jadwal pemberian pakan yang berbeda. Dengan memotong waktu pemberian Artemia 2 - 4 hari dan disubstitusi dengan Tubifex, aktifitas enzim protease, lipase dan amilase pada larva ikan patin, memiliki pola yang sama. Aktifitas enzim cenderung meningkat dan mencapai puncak pada umur 7 hari, selanjutnya terus menurun sampai larva berumur 15 hari. Kelangsungan hidup ikan selama penelitian berbeda-beda untuk setiap perlakuan dengan nilai tertinggi dicapai oleh larva yang diberi pakan Artemia sampai berumur 8 hari. Larva ikan patin belum siap sepenuhnya untuk menerima pakan berupa cacing sutera sejak stadia awalnya. Kata kunci: Enzim, Pencernaan, Patin, Pangasius hypophthalmus